Ferroelectric HfO2 Tunnel Junction Memory With High TER and Multi-Level Operation Featuring Metal Replacement Process - Kobayashi, Masaharu; Tagawa, Yusaku; Mo, Fei; Saraya, Takuya; Hiramoto, Toshiro (IEEE journal of the Electron Devices Society, 2019)
We have investigated device design of HfO 2 -based ferroelectric tunnel junction (FTJ) memory. Asymmetry of dielectric screening property in top and bottom electrodes is the key for high tunneling electroresistance (TER) ratio. Thus, metal and semiconductor electrodes are proposed. There exists a design space of ferroelectric material parameters to achieve high TER ratio under the constraint of depolarizing field. We have developed an FTJ fabrication process to realize the design. Large polarization charge and symmetric switching voltage are obtained by top metal replacement process. High TER ratio >30 and multi-level cell operation have been successfully demonstrated. Retention characteristics is promising, however, endurance characteristics should be improved for reliable operation.